Object recognition deficit in early- and adult-onset schizophrenia regardless of age at disease onset - Azadmehr, Hedieh; Rupp, André; Andermann, Martin; Pavicic, Dinka; Herwig, Kerstin; Weisbrod, Matthias; Resch, Franz; Oelkers-Ax, Rieke (Psychiatry research. Neuroimaging, 2013)
Perceptual closure is the ability of the brain to recognize a complete object based on fragmentary information and has been known to be impaired in schizophrenia. Here, the neural integrity of perceptual closure in schizophrenia with different disease onsets was evaluated by examining the generation of event-related potential (ERP) components (P100, N180, and Ncl). ERPs were recorded from 40 patients (19 early-onset schizophrenia, “EOS” and 21 adult-onset schizophrenia, “AOS”) and 40 age-matched healthy volunteers. Brain electric source analysis (BESA) was applied to localize the cerebral generators underlying perceptual closure. Patients showed an impaired generation of Ncl and P100 components. P100 and Ncl amplitudes were significantly reduced in both AOS and EOS (P<0.01). Moreover, N180 and Ncl amplitudes were significantly increased with age in controls and patients (P<0.01). In the case of the Ncl, there was also a significant interaction (P<0.001) between age and group, indicating a greater age-dependent Ncl increase in controls compared to patients. Visual information processing during perceptual closure is impaired in schizophrenia, regardless of age at disease onset. The combined influence of age and group on the amplitude of the Ncl might support the idea of neurodevelopmental deficits in schizophrenia.